An Achromatic Background Filter for Cytological Image Analysis - Isotani, Sadao; Bonventi Jr., Waldemar (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2009)
In this work we evaluated an algorithm for filtering the achromatic background of colored cytological images. This algorithm makes use of an Isotropic White Locus Chromaticity Diagram, where the white region is selected by polar coordinates in the 1931 Chromaticity Diagram. The potential for application as a background filter is analyzed through applications to cytological images stained with the Papanicolaou method.